A Project Report on An Knowledgement Based Approach for the Detection of Routing Misbehavior in Menets - SHRISHAIL, VEERENDRA, MUNIRAJA S and SANDEEP PATIL (2008)
INTERNAL GUIDE: MOHAMMED SHARIF, MVJCE EXTERNAL GUIDE: HAMSA S, RICT COORDINATON MIND SCT IT
Keywords: Knowledgement Based Approach for the Detection of Routing Misbehavior in Menets